Pengaruh Media Wordwall Games terhadap Berpikir Kritis Siswa Kelas IV di SD Saraswati 1: Penelitian - Putu Wahyu Ligyawati, Ni; Dewi Pusparini, Luh; Ketut Manik Asta Jaya, I (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This scientific exploration is intended to identify the implications of the use of the Open the Box type Wordwall Games on the critical reasoning capacity of grade IV students in the Pancasila Education subject group, especially in the discussion of